TEKNIK PENILAIAN KINERJA DALAM PEMBELAJARAN BIOLOGI DI TINGKAT MADRASAH ALIYAH - Ansori, Achmad Zanuar (Inovasi: Jurnal Diklat Keagamaan, 2016)
The technique of performance assessment in 2013 in curriculum 2013 isused to assess students’ ability to do something. This assessment techniqueis in line with the aim and the characteristics of biology subject at MadrasahAliyah level. As a branch of science, biology has three aspects whichi.e. process, product and attitude. Biology learning is led to reach thosethree aspects. The use of performance assessment technique is in linewith the process aspect in which the Biology learning demands studentsto do scientific performance as a part of learning process. Scientific performance will lead students to learn how Biological knowledge is acquired. So the development ofperformance assessment instruments is really important to be masteredby the teachers of Biology. This is beingmore strengthen by a compulsory assessment on basic competence related to the skill domain as recommended by 2013 curriculum. The steps on developing assessment instrument starts from deciding the skill that will be assessed to thedeveloping observation formand performance assessment rubric is presented on this paper. This article also discuss the position ofperformance assessment based some experts opinions.